COMPARING ATTITUDES TOWARDS BRAND FOR SPONSORED POSTS AND PAID PARTNERSHIPS ON INSTAGRAM IN INDONESIA - Satara, Ashifa; Belgiawan, Prawira Fajarindra (Journal of Business and Management, 2018)
Abstract. Background: Digital advertisements are more commonly used in this age of technology, with Native Advertisements being examples of the more popular forms of digital advertising that is usually encountered on social media. Social media has proven itself to be a useful tool for building brand awareness, however, it has a greater risk of damaging the company reputation which can affect overall consumer’s Attitudes towards Brand. The amount of Instagram users has exponentially grown over the past few years and its overall stability compared to other social media platforms shows its potential as an advertising platform. With companies spending more on Native Advertising, especially on social media, it is important to know the advertising value for using Native Ads and its relation and effect on Attitudes towards Brand. Thus, this research aims to explore the advertising value of Paid Partnership and Sponsored Post and its relationship and effect on Attitudes towards Brand. Methods: The most commonly applied theory to measure advertising value and Attitudes towards Brand is the Ducoffe Advertising Theory which is used in this research. Quantitative method is applied by spreading online questionnaire to 350 Instagram users based in Indonesia. The data is analyzed using Partial Least Squares (PLS) method and Paired Sample t-test. Results: The results show that the Ducoffe Advertising Value theory can be applied to Paid Partnership and Sponsored Post on Instagram and there is a significant positive correlation between advertising value and Attitudes towards Brand. Conclusion: While overall results shows that Paid Partnership generates more positive Attitudes towards Brand compared to Sponsored post, only one out of five constructs of attitudes towards brand is statistically significantly different and subsequent analysis using several subsamples obtained in this study shows that several subsamples prefer Sponsored Post over Paid Partnership. So, the decision to choose which method of Instagram advertising should take in several factors: target audience, budget, goal, and duration of the campaign.Keywords: Advertising Value, Attitudes towards Brand, Digital Advertising, Instagram Paid Partnership, Instagram Sponsored Post, Native Advertising